Childhood trauma and adult mental disorder: A systematic review and meta‐analysis of longitudinal cohort studies. (18th January 2021) - McKay, Michael T.; Cannon, Mary; Chambers, Derek; Conroy, Ronán M.; Coughlan, Helen; Dodd, Philip; Healy, Colm; O'Donnell, Laurie; Clarke, Mary C.
Abstract: Objective: To systematically review evidence for the association between trauma experienced in childhood or adolescence, and the subsequent experience of affective or psychotic mental disorders in adulthood. Methods: Electronic databases (Scopus, Medline (for Ovid), EMBASE and PsychINFO) were searched for peer‐reviewed, longitudinal cohort studies in the English language examining child or adolescent exposure to trauma, and adult‐diagnosed depression, anxiety, psychotic disorder or bipolar disorder. A total of 23 manuscripts were retained. Results: Results revealed a significant association between the following childhood exposures and adult mental disorder: bullying (victimhood, perpetration and frequency); emotional abuse; physical neglect; parental loss; and general maltreatment (unspecified and/or multiple trauma exposure). There was some evidence of a dose‐response relationship with those exposed to multiple forms of maltreatment having more than three times the odds of developing a mental disorder (Odds ratio = 3.11, 95% CI = 1.36–7.14). There was no significant association found between physical or sexual abuse and adult mental disorder; however, this is likely an artefact of how these adversities were assessed. Conclusion: There is strong evidence of an association between childhood trauma and later mental illness. This association is particularly evident for exposure to bullying, emotional abuse, maltreatment and parental loss. The evidence suggests that childhood and adolescence are an important time for risk for later mental illness, and an important period in which to focus intervention strategies.